BREAKING LANGUAGE BARRIERS: EASY AND EFFECTIVE WAYS TO TEACH ENGLISH TO NON-NATIVE SPEAKERS (Ustozlar uchun, 2025)
This article is devoted to the topic “ breaking language barriers: easy and effective ways to teach english to non-native speakers”. The article explores simple and effective strategies for teaching English to non-native speakers. As English has become a global language, learners often face difficulties such as language anxiety, limited vocabulary, and lack of confidence. The article emphasizes the importance of using clear and simple language, encouraging speaking from the beginning, improving listening skills through media, applying games and interactive activities, and creating a supportive learning environment. Practical classroom examples and useful online resources are provided to help teachers make English learning easier and more engaging. The findings suggest that learner-centered and interactive teaching methods significantly improve motivation, confidence, and communicative competence among non-native English learners.